Fire performance of blind-bolted connections to concrete filled tubular columns in tension - Pascual, Ana M.; Romero, Man; Tizani, Walid (Elsevier, 2015)
This paper describes an advanced numerical model to predict the fire behaviour of blind-bolts in the tension area of endplate connections between I-beams and concrete filled tubular (CFT) columns. It is the continuation of a previous research on the thermal response of connections, considering the tension load of a moment-resisting connection. Due to the absence of experiments and data on blind-bolts fire performance the aim was to provide a model for their study. The effect of two main variables was researched, the concrete infill of the columns and the anchored extension of the blind-bolt. The fire resis- tance rating (FRR), the failure mode and the force–displacement–temperature curve at high temperatures were discussed. Results proved that concrete inside the column enhanced the connections response at elevated temperatures in terms of FRR and stiffness. On the other hand, the use of anchored blind-bolts compared with normal blind-bolts provided stiffer connections, but the FRR improvement depended on the plate thickness and steel bolt properties. Finally, the use of fire resistant steel bolts as a method to enhance the fire response was assessed, observing the benefits to these connections when the shank of the blind-bolt governs the failure.